Оцінювання екологічної сталості регіонів України на основі даних 2005 2007 років - Статюха, Геннадій Олексійович; Джигирей, Ірина Миколаївна; Тишенко, Ігор Анатолійович (Eastern-European Journal of Enterprise Technologies, 2009)
This article represents sustainable development assessment methods and approaches classification. Modified Ukrainian Regional Environmental Sustainability Index is proposed. The results of environmental sustainability assessment of Ukrainian regions based on 2005‑2007 data are given.